Descriptive Insight on the Impact of Sales Organisation (Global Journal of Management and Business Research, 2023)
Sales organisation is a critical aspect of any business that aims to achieve success in the market. This research paper aims to explore the importance of sales organisation in a business and its impact on sales growth. The study focuses on the role of sales organisation in creating effective sales strategies, implementing sales plans, and measuring sales performance. The paper also discusses the factors that influence sales organisation effectiveness and provides recommendations for businesses to improve their sales organisation.